Thermo-elastic analysis of axially functionally graded rotating thick truncated conical shells with varying thickness. (1st July 2016) - Jabbari, Mehdi; Nejad, Mohammad Zamani; Ghannad, Mehdi
Abstract: In this paper, distributions of stress and displacement components of rotating truncated conical shells with varying thickness made of functionally graded materials (FGMs) subjected to thermo-mechanical loading are obtained. The materials are assumed to be perfectly elastic and isotropic which are assumed to vary according to the power law function in the axial direction of the conical shell. Based on steady-state heat conduction equation, the higher-order shear deformation theory (HSDT) is used to describe the nature of thermo-elastic behavior of the truncated conical shells. The system of partial differential equations is semi-analytically solved by using multi-layer method (MLM). Numerical results are presented to verify the accuracy of present theory and the influences played by many parameters are investigated.